Conflicts, crop choice, and agricultural investments: Empirical evidence from Nigeria - Amare, Mulubrhan; Abay, Kibrom A.; Berhane, Guush; Andam, Kwaw S.; Adeyanju, Dolapo (Elsevier, 2025)
Conflict remains a major driver of poverty in Africa. Conflicts and political instability in the region have been increasing recently and are drawing more attention in public discourse. While it is widely acknowledged that conflicts disrupt agricultural production and food systems, the full extent of the damage inflicted on the lives and livelihoods of farming households and the mechanisms to redress this harm remain poorly understood. In particular, the link between violent conflicts and households’ land allocation and related agricultural investment decisions remains understudied. In this study, we use geocoded longitudinal data along with detailed agricultural panel household surveys in Nigeria to assess the impact of violent conflicts on crop choice decisions and related agricultural investments. Specifically, we explore how farmers’ land allocation and agricultural investment decisions relate or respond to the outbreak and intensity of violent conflicts. We find that violent conflicts are associated with a reduction in the share of both land area cultivated and area harvested. We also find suggestive evidence that violent conflicts may shape farmers’ crop choices and related investments, as violent conflicts are associated with reduction in the share of land allocated to long-term crops (e.g., perennial crops, trees, roots and tubers). Overall, our findings suggest that violent conflicts can negatively influence farmers’ agricultural investments directly by affecting both land utilization patterns and portfolio allocation across activities with varying returns to investments.